A cross‐sectional study of pet owners' attitudes and intentions towards nutritional guidance received from veterinarians. (3rd December 2020) - Kamleh, May; Khosa, Deep K; Verbrugghe, Adronie; Dewey, Cate E; Stone, Elizabeth
Abstract : Background: Beliefs of pet owners strongly influence their decision‐making surrounding their pets' diet. Thus, nutritional guidance is an essential component of veterinary practice and integral to managing rising rates of pet obesity. This study examined pet owners' trust of, perceived effectiveness of, and intentions to follow nutritional guidance received from their veterinarian in managing their pets' diet. Methods: A cross‐sectional study of 1402 dog and cat owners in the USA and Canada was conducted using an online questionnaire tool. Data were analysed using descriptive statistics and logistic regression modelling. Results: Clients are concerned about the effectiveness of veterinary nutrition recommendations. Cat owners were more likely than dog owners to consider the nutritional guidance they receive from veterinarians effective for their pets' diet (1.75, P=0.04). Length of pet ownership, feeding dry diets and frequency of veterinary visits were all positively associated with owners considering veterinary nutritional guidance to be effective in managing pets' diet. Conclusion: Identifying these perspectives can aid in developing strategies to provide nutrition support to pet owners to improve their perceptions of, self‐efficacy with, and compliance with veterinary nutrition recommendations.